Economic Policy Uncertainty and Financial Innovation: Is There Any Affiliation? - Jia, Zeng; Mehta, Ahmed Muneeb; Qamruzzaman, Md.; Ali, Majid (Frontiers in Psychology, 2021)
The impetus of the study is to gauge the nexus between economic policy uncertainty and financial innovation BRIC nations for the period from 2004:M1 to 2018: M12. The study utilizes both linear and nonlinear Autoregressive Distributed Lagged (ARDL) to evaluate long-run and the short-run association between EPU and financial innovation, furthermore, the causal effects investigate by following non-granger casualty framework. The results of long-run cointegration, i.e., the test statistics of Fpss, Wpss, and tBDM, reject the null hypothesis and establish the presence of the long-run association between EPU and financial innovation. Conversely, long-run asymmetry cointegration revealed with the test statistics of Fpss, Wpss, and tBDM in nonlinear estimation. Furthermore, both in the long-run and short-run, the Wald test results disclose asymmetry effects running from EPU to financial innovation. In regards to EPU asymmetry impact on financial innovation, study documents that positive and negative shocks in EPU negatively linkage with financial innovation in the long-run but short-run effects is insignificant. Besides, financial innovation measured by R&D investment exhibits positive linked with shocks in EPU, implying that uncertainty induces innovation in the economy. Refers to causality effects, the study divulges feedback hypothesis, i.e., bidirectional causality prevail between EPU and financial innovation in all sample countries